ZNF213 Facilitates ER Alpha Signaling in Breast Cancer Cells - Yang, Huijie; Lv, Xulei; Li, Xin; Mao, Lanzhi; Niu, Zhiguo; Wang, Ting; Zhuang, Ting; Huang, Qingsong (Frontiers in Oncology, 2021)
Background Breast cancer is the most common women malignancy worldwide, while estrogen receptor alpha positive type accounts for two third of all breast cancers. Although ER alpha positive breast cancer could be effectively controlled by endocrine therapy, more than half of the cases could develop endocrine resistance, making it an important clinical issue in breast cancer treatment.Thus, decoding the detailed mechanism, which controls ER alpha signaling activation and ER alpha protein stability, is of great importance for the improvement of breast cancer therapy. Several zinc finger proteins were shown to mediate the ubiquitination process and modulate protein stability. Thus, we further explore the function of Zinc finger protein 213 on ER alpha protein stability and tamoxifen resistance. Methods CCK8 and Edu assay was used to measure cell proliferation. RNA sequence was performed by Ingenuity pathway analysis. The ER alpha signaling activities were measured with luciferase assay, real-time quantitative PCR, and western blotting. Protein stability assay and ubiquitin assay were used to determine ER alpha protein degradation and ubiquitination. The immuno-precipitation was utilized to determine ER alpha and ZNF213 interaction. The ubiquitin-based immuno-precipitation assay was sued to detect specific ubiquitination manner on ER alpha. Results We identified ZNF213 as a novel zinc finger protein, which modulated ER alpha protein. ZNF213 expression correlated with poor outcome in endocrine treated patients. ZNF213 depletion inhibited ER alpha signaling and proliferation in breast cancer cells. Further mechanistic studies showed ZNF213 located in cytosol and nuclear, which modulated ER alpha stability via inhibiting ER alpha K48-linked ubiquitination. Conclusions Our study reveals an interesting post-translational mechanism between ER alpha and ZNF213 in breast cancer. Targeting ZNF213 could be an appealing strategy for ER alpha positive breast cancer.